Integrated management of cutleaf teasel (Dipsacus laciniatus) along roadsides in Missouri, USA - Bentivegna, Diego Javier (2012)
Cutleaf teasel is a biennial, invasive weed found along roadsides throughout much of the central USA. Long-term management should, ideally, integrate chemical and cultural practices. Research in Missouri along Interstate Highway 70 was initiated to combine chemical applications with overseeding perennial grasses. A field experiment was carried out with a split-plot design (four replications), where the main plot factor was herbicide applied, and the sub-plot factor was grass species overseeded. Herbicide treatments comprised dicamba þ diflufenzopyr, aminopyralid, triclopyr, and metsulfuron. Grass species included tall fescue þ buffalograss or Canada wildrye þ buffalograss. Cutleaf teasel coverage was reduced from 79% to 93% for all herbicide treatments except triclopyr, 5 months after the last herbicide application. Seedling counts of cutleaf teasel were lowest for aminopyralid by 6 months after the last herbicide application. The herbicide programme that provided 490% cutleaf teasel control and resulted in at least 65% grass establishment resulted in up to a 93% reduction in cutleaf teasel emergence by 363 days after initial herbicide application. Integration of applications of herbicides and desirable seeding grasses are needed over a long period to exclude cutleaf teasel in roadside areas.